2013
DOI: 10.1021/es401864w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acidic Deposition and Soil Acidification on Sugar Maple Trees in the Adirondack Mountains, New York

Abstract: We documented the effects of acidic atmospheric deposition and soil acidification on the canopy health, basal area increment, and regeneration of sugar maple (SM) trees across the Adirondack region of New York State, in the northeastern United States, where SM are plentiful but not well studied and where widespread depletion of soil calcium (Ca) has been documented. Sugar maple is a dominant canopy species in the Adirondack Mountain ecoregion, and it has a high demand for Ca. Trees in this region growing on so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 41 publications
8
95
1
Order By: Relevance
“…Sites with low base saturation experience decreased foliar and forest floor Ca, as well as the potential for increased dieback, reduced sugar maple regeneration, and reduced basal area with increased N deposition or N and S inputs Houle 2013, Sullivan et al 2013). Sullivan et al (2013) found little sugar maple regeneration when B horizon base saturation was below 12 percent; the greatest amount of regeneration occurred when base saturation was greater than 20 percent. Unless species specific information is available, mineral soil base saturation greater than 15 percent is associated with upper critical loads while base saturation less than 15 percent is associated with lower critical loads.…”
Section: Soil Texture and Permeabilitymentioning
confidence: 84%
See 2 more Smart Citations
“…Sites with low base saturation experience decreased foliar and forest floor Ca, as well as the potential for increased dieback, reduced sugar maple regeneration, and reduced basal area with increased N deposition or N and S inputs Houle 2013, Sullivan et al 2013). Sullivan et al (2013) found little sugar maple regeneration when B horizon base saturation was below 12 percent; the greatest amount of regeneration occurred when base saturation was greater than 20 percent. Unless species specific information is available, mineral soil base saturation greater than 15 percent is associated with upper critical loads while base saturation less than 15 percent is associated with lower critical loads.…”
Section: Soil Texture and Permeabilitymentioning
confidence: 84%
“…Sullivan et al (2013) found that a B horizon base saturation of 12 percent was the cut-off below which there was a near absence of sugar maple seedling regeneration. Regeneration…”
Section: Base Saturationmentioning
confidence: 95%
See 1 more Smart Citation
“…Soil collection procedures and physical and chemical analyses were the same as those described by Gauthier et al (2015). The first selection of soil chemical variables to test was based on results from Ouimet et al (2013) and Sullivan et al (2013) on SM health. From the upper 10 cm of B horizon mineral soil, the selected variables were Ca, Mg and total base cation saturation, the Ca/Mg ratio, the K/Mg ratio, and pH (in H 2 O).…”
Section: Climatic Geographic and Soil Variablesmentioning
confidence: 99%
“…Deficiencies of soil calcium and magnesium have been associated with sugar maple decline on the Allegheny Plateau of Pennsylvania and New York (Horsley et al, 2000;Bailey et al, 2004), Green Mountains in Vermont (Schaberg et al, 2006) and the Adirondacks of New York (Sullivan et al, 2013). Leaching losses of soil Ca and Mg are attributed to acid rain caused by air pollution (Driscoll et al, 2001).…”
Section: Introductionmentioning
confidence: 99%